Relevansi Nilai dan Nilai Prediktif pada Penghasilan Saham di BEI - Suwarni Suwarni; Rinto Noviantoro; Ahmad Soleh; Mochammad Fahlevi (Universitas Mercu Buana, 2020)
After the convergence of IFRS in Indonesia, according to Statement of Financial Accounting Standards 1, economic entities are required to provide information about comprehensive income in their financial statements. This regulatory change is expected to improve the quality of earnings as measured by value relevance and predictive value. The purpose of this study is to find out more about the effect of IFRS convergence in Indonesia, especially regarding the presentation of comprehensive income, on the quality of net income and comprehensive income as measured by value relevance and predictive value. Furthermore, the value relevance and predictive value of comprehensive income will be compared with the value relevance and predictive value of net income. This study uses a quantitative approach, with a sample of entities listed on the Indonesia Stock Exchange in 2011-2014, except for companies in the financial sector. The results showed that there was a significant value relevance and predictive value for both comprehensive income and net income. However, when comparing the value relevance and predictive value of the two incomes, it is found that net income is superior to net income. However, it should be noted that the advantages of net income compared to comprehensive income are not significant.